Highly functional ellipsoidal block copolymer nanoparticles: a generalized approach to nanostructured chemical ordering in phase separated colloidal particles. Issue 13 (29th November 2017) - Schmidt, B. V. K. J.; Wang, C. X.; Kraemer, S.; Connal, L. A.; Klinger, D.
Abstract : Spatially controlled introduction of chemical functionalities into ellipsoidal block copolymer nanoparticles is achieved through pre- and post-assembly strategies. Abstract : A new synthetic platform for the spatially controlled functionalization of phase separated block copolymer nanoparticles is presented. Selective incorporation of chemical functionalities into specific domains of striped ellipsoidal nanoparticles is achieved by blending a structure-inducing PS- b -P2VP block copolymer with functionalized PS- co -X and P2VP- co -X copolymers. During self-assembly, the BCP phases incorporate the corresponding functional copolymers which results in their chemical modification without losing control over particle shape and morphology. It was shown that the introduction of benzophenones as photocrosslinking groups allows the preparation of particles which demonstrated a reversible shape change due to triggered swelling/deswelling. This dynamic behavior could be combined with the selective introduction of other moieties such as ferrocene groups or reactive pentafluorostyrene moieties. Ultimately, such combinations opened up new opportunities for post-assembly functionalizations to realize multifunctional particles containing for example ferrocene moieties in the PS domains and Au nanoparticles in the P2VP phase. Overall, a versatile toolbox was developed that enables the formation of tailor-made functional shape anisotropic nanoparticles.